Oral and topical sodium cromoglicate in the treatment of diffuse cutaneous mastocytosis in an infant - Edwards, Alan Martin (BMJ Publishing Group, 2011)
Diffuse cutaneous mastocytosis (DCM) is a rare, severe, variant of cutaneous mastocytosis. The authors report the case of a male infant who developed maculae and maculopapulae on his legs and abdomen when aged 3.5 months, which spread to all body surfaces within weeks. Diagnosis of DCM was made at the age of 6 months when he had developed extensive bullous eruptions, generalised pruritus, flushing and abdominal pain. Treatment was started with oral dimethindine maleate. At the age of 18 months, oral sodium cromoglicate (SCG) was introduced. At the age of 23 months, additional treatment was started with a cutaneous emulsion containing 4% SCG. Continued treatment with oral dimethindine maleate, oral SCG with the dose maintained at 25 mg/kg/day, and SCG 4% cutaneous emulsion applied two to four times daily has resulted in a steady improvement of symptoms and skin appearance.